Fundamentals of financial accounting - Welsch, Glenn A.; Short, Daniel G. (Homewood, Ill. : Irwin, 1987)
This fifth edition of the book retains all of the features that the numerous faculty who have used the prior editions have regarded favorably. It has been substantially updated to reflect changes in business practice, accounting rules, and the economy. The book is designed to give you maximum flexibility in selecting topics and scheduling.
Includes bibliographical references and index.
hza 18/09/2018
Loans
Keywords: Accounting